2014
DOI: 10.1016/j.apgeochem.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate dissolution in Mesozoic sand- and claystones as a response to CO2 exposure at 70°C and 20MPa

Abstract: Keyword: CO 2 experiments, synthetic pore fluid, in situ alterations, reservoir rocks and caprocks, carbonate dissolution, calcite, dolomite, ankerite, siderite, lack of silicate dissolution. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 AbstractThe response to CO 2 exposure of a variety of carbonate cemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Further, the carbonate content in LGW7 is lower than in LGW1 and LGW8 (Figure 2), indicating paleofluid alteration processes including dissolution of carbonate (Aman et al, 2018). Relative solubility of carbonates depends on the fluid composition, as well as pressure and temperature conditions, but may be significant even on relatively short timescales in CO 2 ‐rich fluid systems (Weibel et al, 2014) such as observed in the Green River area of Utah (e.g., Wigley et al, 2012). The observed fluid‐rock alteration effects indicate that the LGW7 fracture has provided an important flow path within the LGW fault damage zone, and the measured geomechanical properties are representative of a fracture exposure to reactive, CO 2 ‐charged brines within a fault in the overburden of a natural CO 2 reservoir (Kampman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the carbonate content in LGW7 is lower than in LGW1 and LGW8 (Figure 2), indicating paleofluid alteration processes including dissolution of carbonate (Aman et al, 2018). Relative solubility of carbonates depends on the fluid composition, as well as pressure and temperature conditions, but may be significant even on relatively short timescales in CO 2 ‐rich fluid systems (Weibel et al, 2014) such as observed in the Green River area of Utah (e.g., Wigley et al, 2012). The observed fluid‐rock alteration effects indicate that the LGW7 fracture has provided an important flow path within the LGW fault damage zone, and the measured geomechanical properties are representative of a fracture exposure to reactive, CO 2 ‐charged brines within a fault in the overburden of a natural CO 2 reservoir (Kampman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As low temperature, low pH, high p CO 2 , and high water/ rock ratio cannot generate a large volume of secondary pores by the dissolution of carbonate minerals, it is not likely that extensive carbonate dissolution will occur in buried sandstone geochemical systems with high temperature and low water/rock ratio. Many studies on water-rock interaction experiments also support this idea when the data were analyzed quantitatively, although dissolution does take place at low/high temperatures (Weibel et al 2014). In addition, the dissolved carbonate minerals were commonly reported to be re-precipitated in long-term numerical simulation experiments (Bertier et al 2006;Liu et al 2012).…”
Section: Experimental Results and Geological Implicationmentioning
confidence: 94%
“…Crushed samples were reacted in bespoke titanium pressure vessels, Figure 2. Each pressure vessel (430 mL) had a gas inlet and a fluid outlet, where the gas inlet was used to supply CO2 into the vessel through a pair of ISCO 500D syringe pumps (USA) running in 'constant pressure' mode (Gunter et al, 1993;Weibel et al, 2014). Four set of batch experiments were conducted for a period of 9 months.…”
Section: Methodsmentioning
confidence: 99%